Liquid relations : contested water rights and legal complexity - Roth, Dik, 1954-; Boelens, Rutgerd; Zwarteveen, Margreet (Rutgers University Press, 2005)
Water management plays an increasingly critical role in national and international policy agendas. Growing scarcity, overuse, and pollution, combined with burgeoning demand, have made socio-political and economic conflicts almost unavoidable. Proposals to address water shortages are usually based on two key assumptions: (1) water is a commodity that can be bought and sold and (2) "states," or other centralized entities, should control access to water. Liquid Relations criticizes these assumptions from a socio-legal perspective. Eleven case studies examine laws, distribution, and irrigation in regions around the world, including the United States, Nepal, Indonesia, Chile, Ecuador, India, and South Africa. In each case, problems are shown to be both ecological and human-made-the locally specific outcomes of social, political, and environmental histories. The essays also consider the ways that gender, ethnicity, and class differences influence water rights and control. In the concluding chapter, the editors draw on the essays' findings to offer an alternative approach to water rights and water governance issues. By showing how issues like water scarcity and competition are embedded in specific resource use and management histories, this volume highlights the need for analyses and solutions that are context-specific rather than universal